2021
DOI: 10.1038/s41467-021-21124-4
|View full text |Cite
|
Sign up to set email alerts
|

Designing a next generation solar crystallizer for real seawater brine treatment with zero liquid discharge

Abstract: Proper disposal of industrial brine has been a critical environmental challenge. Zero liquid discharge (ZLD) brine treatment holds great promise to the brine disposal, but its application is limited by the intensive energy consumption of its crystallization process. Here we propose a new strategy that employs an advanced solar crystallizer coupled with a salt crystallization inhibitor to eliminate highly concentrated waste brine. The rationally designed solar crystallizer exhibited a high water evaporation rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
134
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 200 publications
(136 citation statements)
references
References 44 publications
1
134
1
Order By: Relevance
“…In small- to medium-capacity BWRO systems, ZLD is feasible, but requires a means of salt disposal, which causes increased costs for both the additional energy for treatment and the solid waste disposal [ 86 , 87 , 88 ]. A number of methods have been proposed to lower the energy consumption and costs for ZLD, by combining various membrane and thermal processes [ 89 , 90 , 91 , 92 , 93 , 94 ]. All of the methods, either used or designed to date, cause a major increase in power consumption, resulting in higher water production costs [ 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…In small- to medium-capacity BWRO systems, ZLD is feasible, but requires a means of salt disposal, which causes increased costs for both the additional energy for treatment and the solid waste disposal [ 86 , 87 , 88 ]. A number of methods have been proposed to lower the energy consumption and costs for ZLD, by combining various membrane and thermal processes [ 89 , 90 , 91 , 92 , 93 , 94 ]. All of the methods, either used or designed to date, cause a major increase in power consumption, resulting in higher water production costs [ 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a proof-of concept, a 3D cupshaped solar solute regenerator (3D SR) is designed for solute regeneration. 15 The 3D SR consists of a photothermal cup made of a spectrally selective absorber (SSA). The outer surface of the 3D SR is wrapped by a very thin polyethylene (PE) film to prevent it from directly contacting with the saturated salt solution.…”
Section: Design Principle Of the Nescodmentioning
confidence: 99%
“…Table 2 shows the main composition of physicochemical parameters present in ROC from desalination plants (seawater or brackish). Some authors have shown the structural characteristics of brine components using FTIR, SEM, and TEM [42][43][44]. Furthermore, Sanmartino et al [45] identified the phases present in the used RO brine by semi-quantitative analysis of the characteristic peaks obtained for X-ray diffraction, such as NaCl (67%), MgCl 2 •6H 2 O (15%), CaSO 4 (10%), Mg 3 (SO 4 ) 2 (OH) 2 (3%), Na 2 SO 4 (3%), and CaMg(CO 3 ) 2 (2%).…”
Section: Physicochemical Characteristics Of the Rocmentioning
confidence: 99%